Microclimate and ramulosis occurrence in a cotton crop under three plant population densities in Southern Brazil - Monteiro, J.E.B.A.=700 1 Sentelhas, P.C.; Chiavegato, E.J.
(En, Es)
Ilus., 16 ref.
Keywords: MICROCLIMA; TEMPERATURA DEL AIRE; DURACION; FOLLAJE; COLLETOTRICHUM GOáYPII; RENDIMIENTO; ARGENTINA